Isolation and culture of functional adult human neurons from neurosurgical brain specimens. Issue 2 (17th October 2020) - Park, Thomas I-H; Schweder, Patrick; Lee, Kevin; Dieriks, Birger V; Jung, Yewon; Smyth, Leon; Rustenhoven, Justin; Mee, Edward; Heppner, Peter; Turner, Clinton; Curtis, Maurice A; Faull, Richard L M; et al.
Abstract: The ability to characterize and study primary neurons isolated directly from the adult human brain would greatly advance neuroscience research. However, significant challenges such as accessibility of human brain tissue and the lack of a robust neuronal cell culture protocol have hampered its progress. Here, we describe a simple and reproducible method for the isolation and culture of functional adult human neurons from neurosurgical brain specimens . In vitro, adult human neurons form a dense network and express a plethora of mature neuronal and synaptic markers. Most importantly, for the first time, we demonstrate the re-establishment of mature neurophysiological properties in vitro, such as repetitive fast-spiking action potentials, and spontaneous and evoked synaptic activity. Together, our dissociated and slice culture systems enable studies of adult human neurophysiology and gene expression under normal and pathological conditions and provide a high-throughput platform for drug testing on brain cells directly isolated from the adult human brain. Abstract : Neurosurgical specimens generated cultures of functional adult human neurons, astrocytes and microglia. Cultured neurons formed dense networks and demonstrated mature neurophysiological properties. These neuronal cultures provide the first easily generated dissociated functional human neurons and have many potential applications including in drug testing and neuroscience research. Graphical Abstract: